Quantifying investment facilitation at country level: Introducing a new index - Axel Berger; Ali Dadkhah; Zoryana Olekseyuk (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
This article introduces a new and unique dataset for measuring the adoption of investment facilitation measures at country level. The Investment Facilitation Index (IFI) covers 117 individual investment facilitation measures, clustered in six policy areas, and maps their adoption for 86 countries. This article presents the conceptual and methodological background of the IFI and provides a first analysis of the level of adoption of investment facilitation measures across countries participating in the investment facilitation for development negotiations in the World Trade Organization (WTO). Our dataset reveals novel insights. Countries which have lower levels of adoption belong to the low-income and lower-middle-income country group and are often located in Africa, the Middle East and to some extent Latin America and the Caribbean. The strong correlation between FDI and the IFI score shows that countries with the lowest levels of FDI, and thus in need of policy tools to attract FDI, have the lowest levels of adoption when it comes to investment facilitation measures. Our dataset has direct relevance for current policy discussions on investment facilitation for development in the WTO but also for domestic-level policy-making. Furthermore, the IFI provides the basis for a future research agenda to assess the design and impact of a future WTO agreement.
Keywords: 330; Investitionspolitik; Indexberechnung; Vergleich; WTO-Recht; Entwicklungsländer